Carrageenan based hydrogels for drug delivery, tissue engineering and wound healing. (15th October 2018) - Yegappan, Ramanathan; Selvaprithiviraj, Vignesh; Amirthalingam, Sivashanmugam; Jayakumar, R.
Highlights: Carrageenan hydrogels are versatile biomaterial for various biomedical applications. Different approach for fabrication of carrageenan based hydrogels were summarized. Various biomedical applications of carrageenan hydrogels have been discussed. By adopting unique fabrication methods, therapeutic potential can be harnessed. Abstract: Carrageenan is a class of naturally occurring sulphated polysaccharides, which is currently a promising candidate in tissue engineering and regenerative medicine as it resemblances native glycosaminoglycans. From pharmaceutical drug formulations to tissue engineered scaffolds, carrageenan has broad range of applications. Here we provide an overview of developing various forms of carrageenan based hydrogels. We focus on how these fabrication processes has an effect on physiochemical properties of the hydrogel. We outline the application of these hydrogels not only pertaining to sustained drug release but also their application in bone and cartilage tissue engineering as well as in wound healing and antimicrobial formulations. Administration of these hydrogels through various routes for drug delivery applications has been critically reviewed. Finally, we conclude by summarizing the current and future outlook that promotes the seaweed-derived polysaccharide as versatile, promising biomaterial for a variety of bioengineering applications.